Gold particle geomicrobiology: Using viable bacteria as a model for understanding microbe–mineral interactions. (26th February 2021) - Sanyal, Santonu Kumar; Shuster, Jeremiah
Abstract: The biogeochemical cycling of gold has been proposed from studies focusing on gold particle morphology, surface textures and associated bacteria living on the surface of gold particles. Additionally, it has been suggested that metabolically active bacteria on particles catalyse gold dissolution and gold re-precipitation processes, i.e. fluid–bacterial–mineral interaction within microenvironments surrounding particles. Therefore, the isolation and characterisation of viable bacteria from gold particles can be used as a model to improve the understanding of bacterial–gold interactions. In this study, classical microbiology methods were used to isolate a gold-tolerant bacterium ( Acinetobacter sp. SK-43) directly from gold particles. The genome of this isolate contained diverse (laterally acquired) heavy-metal resistance genes and stress tolerance genes, suggesting that gene expression would confer resistance to a wide range of potentially toxic metals that could occur in the surrounding microenvironment. The presence of these genes, along with genes for nutrient cycling under nutrient-limited conditions highlights the genomic capacity of how Acinetobacter sp. SK-43 could survive on gold particles and remain viable. Laboratory experiments demonstrated that this isolate could grow in the presence of soluble gold up to 20 μM (AuCl3 ) and that >50% of soluble gold was reduced upon exposure. Collectively, these results suggest that Acinetobacter sp. SK-43 (and presumably similar bacteria) could survive the cytotoxic effects of soluble Au from particles undergoing dissolution. This study provides comprehensive insight on the possible bacterial contributions to gold biogeochemical cycling in natural environments.